Belatacept: the challenges with transformational drugs - Vincenti, Flavio (Translational Andrology and Urology; Vol 6, No 2 (April 29, 2017): Translational Andrology and Urology (Global Urology), 2017)
Dr. Westhoff’s commentary on the recent article in the NEJM detailing the 7-year follow up study comparing the outcome of belatacept vs. cyclosporine in kidney transplantation is thoughtful, insightful and balanced (1) The pursuit of a CNI-free regimen that is effective, non-nephrotoxic and lacks the added cardiovascular risks inherent to the CNIs has been frustrating with multiple drugs having failed because of lack of efficacy or safety. The only agent to emerge from 2 decades of clinical trials is belatacept approved by the FDA in 2011. If belatacept offers all the advantages listed by Dr. Westhoff, why then the reluctance by transplant physicians to adopt it for wider use. With any transformative drug, there is a learning curve on how best to use the drug and who is most likely to benefit from it.